On the parametric transverse vibrations of continuous beam on intermediate elastic supports under the action of moving body - Tho, Do Xuan; Khang, Nguyen Van (Vietnam Journal of Mechanics, 1995)
In this text the method of substructures [2] is applied for establishing the vibration equation of beam under the action of moving body. Later an algorithm is built to solve the vibration equation received. From this algorithm a computer program is set up with TURBO PASCAL 6.0 language.